2016
DOI: 10.18203/2394-6040.ijcmph20164746
|View full text |Cite
|
Sign up to set email alerts
|

Substance abuse pattern among medical college students in Tumkur, Karnataka, India: a cross sectional study

Abstract: Background: Globally, there are 2 billion alcohol users, 1.3 billion smokers and 185 million are drug users. These are accounting for 12.4% of all deaths worldwide. The doctors are vulnerable to substance abuse due to their ready accessibility to the substance of abuse. Medical training is identified as full of stress and it is also observed that students undergo tremendous stress during various years of medical training. Repeated use of drugs can damage essential decision making and effect judgment of actions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
5
1
0
Order By: Relevance
“…Mean age of initiation of substance abuse was 20±2 years in our study. Mir AR et al [9] stated majority of their study population started abusing substance from 20-23 years of age which was similar to our results.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Mean age of initiation of substance abuse was 20±2 years in our study. Mir AR et al [9] stated majority of their study population started abusing substance from 20-23 years of age which was similar to our results.…”
Section: Discussionsupporting
confidence: 91%
“…Among the abuser's alcohol was abused more (62.5%). Similar results were seen by Mir AR et al [9] which showed 36.6% of total sample abused alcohol. Also, a study from Kolkata showed alcohol abuse was present in 27% of medical students [5] although comparatively lesser people 2.1% each abused stimulants and hallucinogens each, availability of these newer drugs is of raising concern.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Living away from the family and staying at hostels (as compared to staying with their families) was associated with an increase in substance use, 19 , 25 , 27 , 28 , 72 74 , 80 a finding consistent with the previous research. 50 Staying away from the family has also been associated with heavy episodic drinking and increased severity of alcohol-related adverse consequences.…”
Section: Discussionsupporting
confidence: 90%
“…The maximum number of students get drugs from their friends. Such results were familiar with studies by Mir et al and Jagnany et al where friends and peer pressure were the major source of drug supply and abuse initiation 17,18 . The relationship between money and drug abuse is of particular interest, as the abuser used all of the income for drugs.…”
Section: Discussionsupporting
confidence: 63%